Islamic Education in the Region of Southeast Asia Countries - Umar Dani; Ismail Pane (Rumah Riset Publisher, 2023)
Islamic education in the Southeast Asian region has several very diverse substances. Education is not only a complement, but also a basis for formulating national education goals. Islamic education is mandatory for all Muslims and must be carried out regardless of age or class. Islamic boarding schools, surau and madrasas are clear evidence of the Islamization that has taken place. Islamic education in Southeast Asia has the same goal, namely to improve the quality of humanity and uphold high morals in realizing a good Muslim. This article will discuss the Islamic education system in Southeast Asia.